PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 102081 MANGGA DUA - Citra Kristina D. Simbolon; Darinda Sofia Tanjung; Reflina Sinaga; Rumiris Lumban Gaol; Juliana; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Teams Games Tournament (TGT) learning model on the learning outcomes of Mathematics students in grade IV of SDN 102081 Mangga Dua for the 2024/2025 academic year. This research is based on low test results. This type of research is quantitative research. The type of sample used in this study was saturated sampling. The research sample used is grade IV students totaling 30 students who are also the population of this study. Based on the results of the study, it was shown that there was an influence of the Teams Games Tournament (TGT) learning model on the learning outcomes of Grade IV students of SDN 102081 Mangga Dua from a correlation coefficient test of that is then it was concluded that the alternative hypothesis (Ha) was accepted, where there was a positive and significant influence between the use of the Teams Games Tournament (TGT) learning model on the Mathematics learning outcomes of grade IV students, judging from the results of the t-test where that is , then Ha is accepted. Meanwhile, based on the calculation of the value of the determination coefficient obtained an R Square value of 0.957. This shows that there is a significant positive influence between the use of the Teams Games Tournament (TGT) learning model on the learning outcomes of Mathematics students in grade IV of SDN 102081 Mangga Dua for the 2024/2025 academic year.